CP-121 Analysis of the prescriptions of intravenous immunoglobulins delivered by Saint-Eloi/Guide Chauliac Phamacy of University Hospital of Montpellier. (24th February 2014) - Ponrouch, MP; Roch-torreilles, I; Rosant, D; Rambourg, P
Abstract : Background: Following work in 2009 on the restrictions placed on use outside Marketing Authorisation (MA) indications of intravenous immunoglobulin (IVIG) in our institution, we wanted to know if after 5 years requirements had progressed or not. Indeed, these requirements are still very common and require pharmaceutical validation in line with the good practice benchmark (RBU) IVIG reviewed regularly by the MSNA (the new French Regulatory Agency). These indications are classified into 4 groups: "MA" (group 1), "temporarily acceptable situations" (2) "not acceptable" (3) "insufficient data" (4). Purpose: To determine the distribution of IVIG prescriptions in different groups during the first half of 2013 at our institution. Materials and methods: Data were collected by the pharmacy service using DxCare software. Prescriptions were monitored using Excel. These data were: indications, doses, the cost of treatment for each patient. Results: 143 patients (68 men and 75 women) received one or more IVIG treatments during this period. The departments of the main prescribers are Neurology, Internal Medicine and Haematology/Medical Oncology. Twenty-five indications were found: 32% in group 1, 40% in group 2 and 28% in group 4, no indication of group 3. The cost of all the treatments was 815, 815 €; 161.507 € were for group 4 indications. The net increase in the number of active patients between 2009 and 2013 (143 vs. 76) was connected to the arrival in our establishment of a Haematology/Medical Oncology Department (48% of patients receiving IVIG). The number of therapeutic indications remained basically the same (25 vs. 26). The proportion of group 4 indications has significantly decreased (28% vs. 46%). This decrease can be attributed to several reasons: (1) several indications which were in group 4 five years ago, are now classified as 'temporarily acceptable situations' (group 2) as more studies have been published; (2) the arrival of haematology department has expanded the MA indications, thus proportionally decreasing the group 4 indications; (3) the reimbursement of these treatments, which is directly related to the relevance of indications, limits some prescriptions because the department would have to pay in case of refusal of reimbursement by Social Security. Conclusions: In conclusion, despite a significant decrease, group 4 indications account for a significant proportion of IVIG prescriptions, especially for treating patients who have failed to respond to other treatments, are resistant to conventional treatments, or who have orphan diseases. Each of these directions is subject to validation by the Drug Committee of our hospital. No conflict of interest.